2003
DOI: 10.1097/00006324-200312000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Predicting and Assessing Visual Performance with Multizone Bifocal Contact Lenses

Abstract: Bifocal contact lens designs, when combined with the aberrations of the eye, will not always provide bifocal vision. Visual quality with a bifocal contact lens can be predicted based on a patient's ocular aberrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 15 publications
0
35
1
Order By: Relevance
“…The optimal pupillary distribution for far and near, and the extent to what a particular design interacts with the aberration pattern of the eye has been little addressed. However, previous studies have shown that a given optical design does not produce the same optical through-focus energy distributions in all eyes (Martin & Roorda, 2003). Among other parameters in bifocal lenses, the amount of near add largely determines visual quality both in terms of visual acuity (de Gracia, and perceived image quality .…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
See 1 more Smart Citation
“…The optimal pupillary distribution for far and near, and the extent to what a particular design interacts with the aberration pattern of the eye has been little addressed. However, previous studies have shown that a given optical design does not produce the same optical through-focus energy distributions in all eyes (Martin & Roorda, 2003). Among other parameters in bifocal lenses, the amount of near add largely determines visual quality both in terms of visual acuity (de Gracia, and perceived image quality .…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 97%
“…While some studies have measured through-focus retinal image quality, generally using double-pass imaging techniques (Artal, Marcos, Navarro, Miranda, & Ferro, 1995;Kawamorita & Uozato, 2005;Navarro, Ferro, Artal, & Miranda, 1993) or visual quality (Gupta, Naroo, & Wolffsohn, 2009;Maxwell, Lane, & Zhou, 2009;Schmidinger et al, 2006;Woods, Woods, & Fonn, 2015), these are generally restricted to patients implanted or fitted with commercial lenses, and therefore limited to specific conditions. Most of the systematic evaluations of many of the available lenses are limited to optical computer simulations and on bench experiments, therefore lacking from the optical and the neural complexity of a patient (Martin & Roorda, 2003).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In addition to routine contact lens fit data (including pupil size), ocular aberrations may also influence presbyopic contact lens performance and acceptance [5][6][7]. Simultaneous image design multifocal contact lenses induce concentric zones of varying power or transition in power within the pupil, altering aberrations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ocular aberrometry has been used for studying ocular properties as a function of accommodation [1], aging [2,3], or refractive error [4], as well as for the assessment of refractive correction techniques (refractive surgery [5,6], cataract surgery [7,8], and contact lenses [9][10][11]), or the correction of ocular aberrations to visualize the eye fundus [12][13][14]. The evaluation of the optical outcomes of refractive surgery has led to an increasing importance of aberrometry in recent years, and commercial aberrometers are now commonly used to assist in surgery [15,16].…”
Section: Introductionmentioning
confidence: 99%